Method to Detect the Cellular Source of Over‐Activated NADPH Oxidases Using NAD(P)H Fluorescence Lifetime Imaging. Issue 1 (3rd April 2017) - Bremer, Daniel; Leben, Ruth; Mothes, Ronja; Radbruch, Helena; Niesner, Raluca
Abstract: Fluorescence‐lifetime imaging microscopy (FLIM) is a technique to generate images, in which the contrast is obtained by the excited‐state lifetime of fluorescent molecules instead of their intensity and emission spectrum. The ubiquitous coenzymes NADH and NADPH, hereafter NAD(P)H, in cells show a short fluorescence lifetime ≈︀400 psec in the free‐state and a longer fluorescence lifetime when bound to enzymes. The fluorescence lifetime of NAD(P)H in this state depends on the binding‐site on the specific enzyme. In the case of NADPH bound to members of the NADPH oxidases family we measured a fluorescence lifetime of 3650 psec as compared to enzymes typically active in cells, in which case fluorescence lifetimes of ∼2000 psec are measured. Here we present a robust protocol based on NAD(P)H fluorescence lifetime imaging in isolated cells to distinguish between normally active enzymes and NADPH oxidases, mainly responsible for oxidative stress. © 2017 by John Wiley & Sons, Inc.